A framework for implementation of a web-based learning management system - Nishtar, Fazidah; Abdul Rahman, Azizah (2006)
This study focuses on the process of implementing and supporting a web-based e-learning system which uses Learning Management System (LMS) methods. The outcome of this study will be a comprehensive framework detailing the procedure and methods involved in implementing the web-based Learning Management System effectively. This framework will be based upon current internationally accepted specifications and practices. Ultimately, it is hoped that we can have more quality Learning Management System developed for the learners so we will be able to achieve better education levels.